2002
DOI: 10.1302/0301-620x.84b8.13447
|View full text |Cite
|
Sign up to set email alerts
|

Lateral unicompartmental knee replacement: Survivorship and clinical experience over 21 years

Abstract: We describe 88 knees (79 patients) with lateral unicompartmental osteoarthritis which had been treated by the St Georg Sled prosthesis. At a mean follow-up of nine years (2 to 21) 15 knees had revision surgery, nine for progression of arthritis, six for loosening, four for breakage of a component and four for more than one reason. Six patients complained of moderate or severe pain at the final follow-up. Only five knees were lost to follow-up in the 21-year period. We performed survivorship analysis on the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 17 publications
(22 reference statements)
5
56
0
7
Order By: Relevance
“…Besides osteotomy for correction of a valgus deformity [17], surgical treatment of lateral femorotibial OA includes either total or unicompartmental arthroplasty [5,11,13,17,21]. When there is full loss of cartilage in the affected compartment, UKA may offer an alternative to TKA when the other compartments are preserved with the potential advantage of reduced morbidity and preservation of bone stock [2,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides osteotomy for correction of a valgus deformity [17], surgical treatment of lateral femorotibial OA includes either total or unicompartmental arthroplasty [5,11,13,17,21]. When there is full loss of cartilage in the affected compartment, UKA may offer an alternative to TKA when the other compartments are preserved with the potential advantage of reduced morbidity and preservation of bone stock [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mean followup (12.6 ± 4.2 years) is one of the longest reported in the literature with patients followed over 23 years (Fig. 4A-B) [5,13,17,22,27,30,32,33]. Finally, to consider the changes concerning the implants and the indications over time, we performed a direct comparison of the survivorship between the group of patients operated on before 1989 and the group of patients operated on after 1989.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lateral UKA reportedly is performed approximately 10 times less frequently than a medial UKA [35] and therefore there is limited literature regarding the outcome of lateral UKAs. In a recent review [18] of lateral UKAs, nine retrospective studies were identified, of which four involved fewer than 20 patients; 83 patients were analyzed in the largest study [6]. In that study, the cumulative survival rates for a lateral UKA were 83% at 10 years and 74% at 15 years.…”
Section: Introductionmentioning
confidence: 99%